The acute effects of whole-body vibration on fencers' special abilities - Chang, C. Y.; Hung, M. H.; Ho, C. S.; Lin, K. C. (Perceptual and Motor Skills, 2019)
The purpose of this research was to study the effects of a whole-body vibration (WBV) warm-up for improving fencers' performance on variables derived from a lunge reaction test, the 10-meter sprint, and the countermovement jump. We compared fencer performances at four time intervals: (a) preintervention, (b) immediately postintervention, (c) 1-minute postintervention, and (d) 2-minute postintervention. Study participants were 16 male fencers. The vibration frequency was 30 Hz, and its amplitude was two mm. After each WBV session, participants significantly improved their performance on all measures at both one and two minutes after the intervention. Specifically, lunge reaction tests scores improved by 5.50% and 7.34%, respectively, relative to preintevention testing (p < .01), peak power output improved by 4.94% and 11.52%, respectively (p < .05), and maximum rate of force development improved by 13.41% and 18.38%, respectively (p < .01). Acute WBV (frequency = 30 Hz, peak-to-peak amplitude of two mm) induced neuromuscular activation and improved lunge reaction scores, agility, and power.